2001
DOI: 10.1046/j.1365-2672.2001.01337.x
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of Campylobacter in New Zealand recreational and drinking waters

Abstract: Aims: To use a published polymerase chain reaction (PCR) method for the detection and identi®cation of thermotolerant Campylobacter species (Camp. jejuni, Camp. coli and Camp. lari) in tandem with a Most Probable Number (MPN) technique to enumerate these species in water samples. Methods and Results: An initial study of 42 river water samples compared the use of conventional culture and PCR methods for the detection of Campylobacter in MPN enrichment tubes. It was found that all samples positive by culture wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 20 publications
4
112
0
Order By: Relevance
“…In outbreak 1 C. jejuni was detected by using a 4,000-ml tap water sample, and in outbreak 3 campylobacters were detected in a drinking water source when 8,000-to 10,000-ml samples were used but not when a 5,000-ml sample was used. Savill et al (28) showed that low campylobacter counts (maximum, 0.3 CFU/100 ml) occurred in their drinking water samples collected in nonepidemic situations. In our study, campylobacters were also detected by enrichment from a 100-ml sample of dike water, and an MPN count of 9 CFU/100 ml was detectable.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In outbreak 1 C. jejuni was detected by using a 4,000-ml tap water sample, and in outbreak 3 campylobacters were detected in a drinking water source when 8,000-to 10,000-ml samples were used but not when a 5,000-ml sample was used. Savill et al (28) showed that low campylobacter counts (maximum, 0.3 CFU/100 ml) occurred in their drinking water samples collected in nonepidemic situations. In our study, campylobacters were also detected by enrichment from a 100-ml sample of dike water, and an MPN count of 9 CFU/100 ml was detectable.…”
Section: Discussionmentioning
confidence: 98%
“…C. coli was found in fecal samples from all 10 pigs. Ducks are known avian sources of C. jejuni and C. coli, and C. coli commonly colonizes the porcine gut (28). Continuous fecal contamination of a drinking water source by several serotypes that are different from those identified in patients has also been seen in other waterborne campylobacter outbreaks (16).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of Campylobacter species associated with foodborne illness, such as C. jejuni and C. coli, are continually measured in water systems worldwide . Since most species of Campylobacter tend not to exist naturally in the environment, but derive from direct fecal deposition, pasture runoff, and sewage outflow, (Obiri-Danso, 1999;Savill, 2001;Eyles, 2006;Fong, 2007;Sopwith, 2008;Schang, 2012) the potential for human infection remains high. Jones et al (2001) provide an excellent review of research regarding Campylobacter in water, sewage and the environment ).…”
Section: Watermentioning
confidence: 99%
“…Programme (FMRP) was obtained to derive recreational freshwater guidelines suitable for New Zealand conditions, extending work reported by Savill et al (2001). For technical reasons, and because there was a need to develop pathogen profiles for New Zealand waters (as noted above), an epidemiological approach using bacterial indicators was ruled out (McBride et al 1996) -despite the fact that swimmers' health studies had been carried out for New Zealand coastal beaches, with some success (McBride et al 1998).…”
Section: Funding For a Freshwater Microbiological Researchmentioning
confidence: 99%